ABCA1 Expression Is Upregulated in an EMT in Breast Cancer Cell Lines via MYC-Mediated De-Repression of Its Proximal Ebox Element - Prijic, Sara; Chang, Jeffrey T. (Biomedicines, 2022)
The ATP-Binding Cassette transporter A1 (ABCA1) reverse cholesterol transport channel has been associated with a number of phenotypes in breast cancer, including reduced proliferation and increased metastatic capacity. It is induced in an epithelial–mesenchymal transition (EMT), but little is known about how this occurs, and whether it is sufficient to promote metastatic phenotypes. To address these questions, we have deciphered the transcriptional regulation of ABCA1 across EMT states and found that it is repressed by MYC via an E-box element in its P1 alternative promoter. De-repression of the promoter by MYC knockdown leads to induction of ABCA1 expression. This indicates that ABCA1 expression is regulated in an EMT, revealing another link between ABCA1 and malignant phenotypes.